Uma avaliação da proposta de reforma tributária do governo FHC - Ávila, Lucimar Antônio Cabral de (2002)
The subject of this investigation is the FHC Government Tax Reform Proposal and its various versions, starting with the year 1995, when the actions of the Federal Government started to show evidence of gradual restructuring of the National Tax System. To this end, we present the changes in the forms of taxation in Brazil since the establishment of the Military Government, characterizing the extreme centralization of competences imputed by the 1966 Reform. The tax changes had a sense of boosting industrial development, notably at the time of the “Economic Miracle”, through the attempt to redesign fiscal federalism, pursued by the 1988 Constitution, until a period of massive use of tax tooling aimed at supplant the immediate need for financial resources to fulfill the obligations of the Brazilian State. This was via the use and manipulation of Social Contributions levied on all stages of production and marketing, imputing to the current Tax System a high degree of regressiveness. We highlight the propositions contained in the Tax Reform Proposal presented in 1999, along with their adaptive versions released in 1999, 2000 and 2000. We investigated the nature, form and possible effects of the proposed changes, both as an alternative for structuring a fairer and more equitable system and as a financing model for public spending. We conclude that, during the discussion process of its Tax Reform Project, the FHC Government sought to generate conditions conducive to the maintenance of the Union's financial equilibrium, regardless of the harmfulness attributed to taxation methods, leading to the favorable actions taken. a gradual implementation of part of the fundamentals contained in the your proposal.